PENINGKATKAN KEAKTIFAN PESERTA DIDIK MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT DENGAN MEDIA WORD SEARCH PUZZLE - Fauziah, Farah Dhiba; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2023)
This classroom action research is to increase the activity of students in class The design of this research is Classroom Action Research (PTK) with research subjects of 35 students. This research refers to the Kemmis and Mc Taggart PTK model, which was carried out in two cycles. Each cycle includes planning, implementation, observation and reflection activities. The success criteria for this research is that 75% of students have learning activities in the high category. The variables of this research are the application of TGT with Word Search Puzzle media and active learning. Data collection techniques use observation, questionnaires and documentation. In accordance with the data collection technique, the data collection instruments used were observation sheets, questionnaires and task checklists. The collected data was then analyzed using quantitative descriptive techniques with percentages. The results of this research show that in cycle I as many as 66.4% of students were in the high learning activeness category. This percentage increased to 91.8% in cycle II. Thus it can be concluded that the action hypothesis formulated is acceptable. So the application of the Teams Games Tournament learning model with Word Search Puzzle media can increase students' active learning.